2004
DOI: 10.1023/b:nere.0000010453.96832.97
|View full text |Cite
|
Sign up to set email alerts
|

Content and Concentration of Taurine, Hypotaurine, and Zinc in the Retina, the Hippocampus, and the Dentate Gyrus of the Rat at Various Postnatal Days

Abstract: Taurine and zinc possess neurotrophic and neuroprotective properties, and they have been demonstrated to interact in the central nervous system (CNS). The aim of this work was to determine taurine, hypotaurine, and zinc levels during postnatal development and any possible significant correlation between them in selective areas of the CNS with differential taurine level regulation and intrinsic capacity to proliferate. Taurine and hypotaurine content (nM/region) and concentration (nM/mg protein) and total zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The non‐protein inhibitory amino acid taurine is present in high concentration in immature brain and decreases with age (Lima et al . ; Kulak et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The non‐protein inhibitory amino acid taurine is present in high concentration in immature brain and decreases with age (Lima et al . ; Kulak et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A 10 roller peristaltic pump was used to supply the gas with the sample solution. Atomic line for zinc was 213.856 nm (3).…”
Section: Methodsmentioning
confidence: 99%
“…This amino acid is known to be involved in the mediation of multiple functions, such as osmoregulation, modulation of calcium fluxes, neuromodulation, protection from oxidative stress, modification of protein phosphorylation, membrane stabilization, affectation of cell migration in the brain and the retina, regulation of axonal outgrowth, elevation in the number of regenerating retinal cells after nerve lesion, and production of neural protection in certain neuropathies (2)(3)(4). Thus, taurine possesses neuroprotective and neurotrophic properties in the central nervous system (CNS) during development and regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine (2‐aminoethanesulphonic acid) is an important amino acid derivative for vertebrates, with beneficial effects on mammals being extensively studied for several decades (Di Leo et al., ; Hayes, Carey, & Schmidt, ; Hayes & Trautwein, ; Huxtable, ; Knopf, Sturman, Armstrong, & Hayes, ; Kuzmina, Gavrovskaya, & Ryzhova, ; Lourenco & Camilo, ; Stapleton & Bloomfield, ). However, only recently have the effects of taurine on fish physiology (osmoregulation, antioxidation, feeding stimulation, and vision) and metabolism been extensively researched (El‐Sayed, ; Huxtable, ; Kim et al., , ; Lima, ; Militante & Lombardini, ; Schaffer, Takahashi, & Azuma, ). Nutritional requirement studies have shown that taurine is an essential or conditionally essential nutrient for various life stages of marine fish and some freshwater fish (Gaylord, Teague, & Barrows, ; Hawkyard, Laurel, Barr, Hamre, & Langdon, ; Hawkyard, Stuart, Langdon, & Drawbridge, ; Jacobsen & Smith, ; Jirsa, Davis, Salze, Drawbridge, & Rhodes, ; Jirsa, Stuart et al., ; Kim et al., ; Salze, McLean, & Craig, ; Takagi et al., ; Takeuchi, ; Yokoyama, Takeuchi, Park, & Nakazoe, ).…”
Section: Introductionmentioning
confidence: 99%